Guaman Poma de Ayala and the Andean logic of conciliation - Dejo, Juan (1990)
​At the beginning of Peruvian colonial period, the time of misunderstanding among the Spaniards and the Andean population was opened. The author, far from conflictive perspective of analysis, shows some signs of the political thought of the Andean people at these times. Guaman Poma de Ayala, in the seventeenth century is one of the smartest chronists in the Andean world. His chronicle, The Nueva Cronica y Buen Gobierno starts the political thought in the mentality, with the message of the conciliation between the two worlds, "la república de españoles y la república de indios".